For the sake of the future: Can democratic deliberation help thinking and caring about future generations? - Kulha Katariina; Leino Mikko; Setälä Maija; Jäske Maija; Himmelroos Staffan (MDPI AG, 2022)
This article examines whether democratic deliberation can enhance participants’ capacity to consider future generations’ perspectives and willingness to make sacrifices to ensure their well-being. In addition to normal deliberation, we are interested in the effects of a mental time travel exercise where deliberators imagine themselves in the future (without ageing). The study is based on an experiment conducted as a part of Citizens’ Assembly that contributed to the long-term planning of the Satakunta region in Finland. Our findings suggest that deliberation as such increases participants’ willingness to consider future generations’ perspectives in long-term planning; yet the mental time travel exercise had only a modest impact on perspective-taking. The results also show some support for the assumption that deliberation can enhance willingness to make sacrifices for future generations, although we do not see such an impact in case of an intergenerational conflict in flood protection. View Full-Text
Keywords: deliberation; future generations; future design